Tissue Culture in Science and Society - Wilson, D. author. aut Link
X, 183 p.
Keywords: This book charts the social and cultural history of the scientific technique known as 'tissue culture'. It shows how tissue culture was a regular public presence in twentieth-century Britain, and argues that history can contribute to current debates surrounding research on human and animal tissue.